An investigation on the particulate number and size distributions over the whole engine map from an optimized combustion strategy combining RCCI and dual-fuel diesel-gasoline. (15th May 2017) - Benajes, Jesús; García, Antonio; Monsalve-Serrano, Javier; Boronat, Vicente
Highlights: Optimized dual-mode dual-fuel strategy to cover the whole engine map. High coherence between smoke and total particles number for diffusive dual-fuel mode. Fully premixed RCCI regime dominated by small particles of 30 nm diameter peak. Highly premixed RCCI mode has a transitional behavior with two particle diameter peaks. Abstract: Literature demonstrates that, for premixed low temperature combustion concepts, particulate matter cannot be directly extrapolated from soot emissions measurements, as typically done for conventional diesel combustion. This is because the particulate matter from low temperature combustion has low fraction of carbonaceous compounds and great amount of soluble organic fraction, which is not captured by the smoke measurement techniques such as the optical reflectometry. By this reason, the study of the particulate matter characteristics from this combustion techniques requires using specific equipment. The aim of the current work is to gain understanding on the particulate matter characteristics from the dual-mode dual-fuel combustion, which is an optimized combustion strategy that combines fully and highly premixed RCCI regimes at low and medium loads, and switches to dual-fuel diffusion combustion at full load. The study was performed over the whole engine map, using a 15.3:1 compression ratio medium-duty EURO VI diesel engine. In particular, the particulate number and size distributions were sampled using a scanning mobility particle sizer and a condensation particle counter, which allow measuring the size distribution and total number of particles from 5 to 250 nm. Results demonstrate that the fully premixed RCCI combustion is dominated by small particles (less than 30 nm in mobility diameter), the dual-fuel diffusion mode is dominated by larger particles (around 100 nm in mobility diameter) showing more diesel-like particle size distributions, and the highly premixed reactivity controlled compression ignition regime shows a transitional particle size distribution with two peaks of mobility diameters around 20 and 80 nm.